A Technology-Enhanced Coaching Model for Professional Readiness in Psychology Education - Dubinskyi, Serhii; Prusak, Pavlо; Pashchenko, Valentyna; Sukhoversha, Maryna; Kastornykh, Iliia (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study aims to develop and empirically evaluate a technology-enhanced, coaching-based learning model to strengthen psychology students’ competencies in providing motivational support, addressing gaps in experiential training and improving graduates’ professional readiness. Methodology: The research employed a quasi-experimental design with one hundred twenty psychology students. The experimental group participated in a structured pedagogical intervention that integrated interactive coaching workshops, video-recorded role-playing simulations of client sessions, etc. Professional readiness was assessed using validated scales measuring professional self-identity, professional competence, client motivation support skills, and coaching self-efficacy. Statistical analysis included descriptive statistics, Student t-test, analysis of variance, correlation and regression analyses, and mediation analysis using Hayes' PROCESS macro. Main Findings: Participants in the experimental condition demonstrated statistically significant and substantial improvements in professional self-identity, coaching self-efficacy, and competence in providing motivational support compared to the control group. The effect sizes were large. Mediation analysis confirmed that enhanced professional competence fully mediated the positive effect of the training on motivational support skills. Novelty of this study: This research contributes to the fields of educational technology and instructional design by introducing an evidence-based, scalable pedagogical model. It positions coaching not as a supplementary activity but as a core instructional methodology, systematically supported by accessible digital tools to enhance reflective learning and feedback. The proposed model offers a practical framework for competency-oriented curriculum redesign in higher education, readily adaptable to hybrid and fully online learning environments, with applicability extending beyond psychology to other professions requiring motivational support skills.